An Embedded IoT-Based System for Real-Time NPK Soil Quality Monitoring in Precision Agriculture - Fathima, Noor; Kumar, S. B. Vinay; Bagali, Mohmad Umair (Engineering, Technology & Applied Science Research, 2026)
This study presents a soil quality evaluation framework that incorporates a JXCT NPK sensor, a pH electrode, a temperature detector, and an Arduino unit capable of real-time monitoring of nutrients. Traditional soil testing techniques are still slow, labor-intensive, and not available to most rural farming communities. The proposed system overcomes these drawbacks by integrating multi-parameter sensing and local and remote visualization using an LCD and an Android application. Mathematical modeling of the electrochemical and optical principles of sensing, linear calibration functions, and equations of nutrient balancing support the hardware. Five types of common soil were experimented on, including sandy, clay, loamy, peaty, and silty soils. Nitrogen (N), Phosphorus (P), Potassium (K), pH, and temperatures were compared to agricultural reference standards, and absolute percentage errors were calculated. The findings indicate high accuracy for nitrogen and phosphorus (0–15% and 10–33% error ranges). However, K measurements exhibited significant deviation (>50%) due to ionic cross-sensitivity. Consequently, the system is recommended for quantitative analysis of nitrogen and phosphorus, but strictly for qualitative trend monitoring regarding potassium levels. The two-screen system (LCD and Android app) was proven to have a stable real-time performance. The results support the promise of embedded sensing systems based on low-cost devices to facilitate precision agriculture and enhance decision-making on fertilizers, especially in areas with scarce resources.